PEMBELAJARAN BAHASA SENTANI UNTUK ANAK MENGGUNAKAN CERITA RAKYAT DI SEKOLAH ADAT SENTANI HOBONG, KABUPATEN JAYAPURA - Wigati Yektiningtyas; Grace J.M. Mantiri (LPPM Uncen, 2020)
Sentani language used by Sentani people in Jayapura Regency is one of 300 local languages in Papua that is not actively used by most Sentani people, especially children. Preservation of Sentani language by teaching it again is needed especially for children so they will not lose their identity. This Community Service is dissemination of a PDUPT research 2017 entitled “Preservation of Sentani Language for Children using Folktales in Jayapura Regency, Papua” founded by the Ministry of Research, Technology and Higher Education of Republic of Indonesia. One of the research output is a text book of Sentani language teaching for children. This book is used to teach Sentani Language for children in Sentani Customary School in Hobong, Central Sentani, Jayapura Regency. This activity is an initiative of infusing folktales to teach Sentani language for children. Besides involving children, this activity also involved the teachers of the school. Using folktales children learned (1) pronunciation, (2) vocabularies, (3) clause, (4) simple sentences, and (5) counting system. Folktales were also used to introduce them to Sentani’s socio-culture and as media of character building. Keywords: folktales, preservation, Sentani language